Oral and written language in autism: theoretical and pedagogical perspectives - Ney, Thaís; Hubner, Lilian Cristine (The ESPecialist, 2022)
The article aims at discussing how the development of language in the Autism Spectrum Disorder (ASD) occurs considering oral language acquisition and writing learning, and which pedagogical methods may be used to foster the process of teaching and learning of students with this diagnosis in Elementary School. The bibliographic research detected a gap in studies on how the oral language acquisition takes place, and, mainly, on how writing learning occurs in this population. The use of visual material to foster the development of oral and written abilities, as well as of direct instructions seem to be effective pedagogical practices to promote linguistic development in the ASD.